EFEKTIFITAS FOOT HAND MASSAGE TERHADAP NYERI POST SECTIO CAESAREA - Pepi " Handayani; Sri " Utami; Sofiana " Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Cesarean-section is a labor in which the fetus is delivered through an incision in the abdomen that causes post cesarean-section pain. Foot hand massage is a non-pharmacological pain management of massaging on the feet and hands that gives stimulation to the central analgesic system and stimulates the release of endorphins. This study is aimed to determine effectiveness of foot hand massage on post cesarean-section pain. The method of the research is "quasi experiment" with "non-equivalent control group" design. The study conducted in post cesarean-section women in Camar I Arifin Achmad Hospital, Pekanbaru. The sampling technique uses a purposive sampling technique by observing the inclusion criteria. The number of samples is 34 respondents which are dividing into 17 experimental groups and 17 control groups. The instrument that uses in both of the group is numeric rating scale. The analysis uses univariate and bivariate analysis by using dependent t test and independent t test. The result of univariate analysis shows that from 34 post cesarean-section women, there are 24 respondents in age 20 – 35 (70,6%), 9 malay and bataknese respondents (26,5%) and 19 respondents who have a cesarean-section at the first time (55,9%). The result of bivariate shows a significant difference of pain range between the experimental group after foot hand massage and a control group without foot hand massage with p value (0,000) < α (0,05), it means that foot hand massage is effective on post cesarean-section pain. Based on the result, foot hand massage is recommended as a complementary therapy for post cesarean-section pain. Keywords: Cesarean-section, foot hand massage, numeric rating scale, pain, cesarean-section